Analisis Keterampilan Smash - Miftahudin, Ilham; Nurhidayat, Nurhidayat (Jurnal Porkes, 2022)
The purpose of this study was to determine the level of high school skills in UKM students of Muhammadiyah University of Surakarta.  The survey method and data collection techniques for tests and measurements Nurhasan.  The results of this study are based on the results of the Descriptive Analysis of Data frequency and are stated in the form of Percentages and the results of the Descriptive Analysis of Smash Open 1 sample are in the interval 17.16 or fall into the very good category with a score of 2.50%, 11 samples  are in the interval 13.05-17.16 or good category with a score of 27.50%, 15 samples are in the interval 8.93-13.04 or moderate category with a score of 37.50%, 12 samples  are in the interval 4.80-8.92 or in the bad category with a score of 30.00%, and 1 sample is included in the interval < 4.80 or in the very bad category with a score of 3.00%.  And for Smah Semi, 4 samples are in the interval 18.38 or in the very good category with a score of 10.00%, 9 samples are in the interval 13.70-18.38 or good category with a score  of 22.50%, 10 samples were in the interval 9.10-13.69 or the moderate category with a score of 25.00%, 15 samples were in the interval 4.32-9.00 or the poor category with the acquisition of scores  by 37.50%, and 2 samples fall into the interval < 4.32 or very bad category with a score of 5.00%.